STRATEGI PEMASARAN PRODUK IJARAH MUNTAHIYAH BITTAMLIK DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF DI BMT GUMARANG AKBAR SYARIAH AMPENAN - Wati, Via Widia; Zihab, Zihab; Hadiyani, Baiq; Sanusi, Muhammad; Adawiyah, Radiatun (widya balina, 2021)
This study aims to explain the application of ijarah Muntamlik (IMBT) financing to BMT Gumarang Akbar Ampenan Syariah as one of the Islamic financial institutions that has products based on the IMBT contract, and implements its strategy in accordance with sharia principles and provisions that apply in Indonesia, namely the DSN-MUI Fatwa No.27/DSN-MUI/III/2000 concerning Ijarah. The results of this study indicate that the implementation of the IMBT strategy is mostly in accordance with the implementation of the IMBT transactions, most of which are in accordance with the matters regulated in these provisions, although there are some things that are not in accordance with the DSN-MUI Fatwa. The discrepancy lies in the recognition of maintenance expenses carried out by the lessee (mustajir) while the burden should be the responsibility of the lessor (mujjir).